Reaction of oats F2 hybrids on Al3+ toxicity - Batalova, Galina; Lisitsyn, Eugene (MTT, 2004)
The opportunity of aimed transfer of the level of aluminum resistance from parents to hybrids by different combination of crosses is very important for breeders. For this purpose, it is necessary to consider nature of distribution of plants of hybrid and parent populations by level of resistance and to calculate quotients of heritability of used parameters of selection. We used oats varieties Colt, Wilma, Charlotte and Argamak as parents and nine different hybrids between them. Estimation of resistance levels was conducted according to Lisitsyn (2000). Degree of dominance and degree of heritability defined under the formulas Pert, Frey (1966). The research has shown that there were hybrid plants with a level of resistance retiring for limits of variation of parent levels of resistance. The direction of cross had significant influence on obtained results. The significance of influence of a maternal plant indicates a participation of cytoplasmic genes in adaptive process. In most cases, the ratio of an inheritable diversity in the tested populations was very great. The nature of dominance of a level of aluminum resistance for different crosses considerably differed. The hybrid Colt õ Argamak displayed full positive dominance, and hybrid Argamak õ Colt - positive overdominance. The overdominance was characteristic for hybrid Wilma õ Argamak too. In any other crosses given varieties promoted development of negative dominance and overdominance. The nature of distribution of seedlings aluminum resistance not always looks like unimodal curve that can indicate the influence of several genes (genetic systems) on studied index. The data of research pointed out a possibility of deriving of highly resistant plants not only by crossing of parent varieties contrast on studied index, but also parent varieties with similar levels of potential aluminum resistance. Lisitsyn, E.M. 2000. Journal of Plant Nutrition 23: 793-804; Pert, F.C., Frey, K.J. 1966. Crop Science 6: 259-262.
Keywords: Ko; aluminium; heredity; hybrids; oats; resistance